2005
DOI: 10.3766/jaaa.16.9.11
|View full text |Cite
|
Sign up to set email alerts
|

Vent Configurations on Subjective and Objective Occlusion Effect

Abstract: The current study reexamined the effect of vent diameters on objective and subjective occlusion effect (OE) while minimizing two possible sources of variability. Nine hearing-impaired participants with primarily a high-frequency hearing loss were evaluated. Laser shell-making technology was used to make ear inserts of completely-in-the-canal (CIC) hearing aids for the study. This was to minimize any potential slit leakage from the inserts. The vent dimensions were systematically altered during the study. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 4 publications
1
37
0
Order By: Relevance
“…2 that the SPL increase caused by occlusion effect occurs in the lower frequencies of the speech bandwidth. This transfer function is only an approximation of the SPL increase caused by occlusion effect, but it is generally consistent with other similar measurements made by [2] or [3].…”
Section: An Active Hearing Protection Device For Musicians Introductionsupporting
confidence: 76%
“…2 that the SPL increase caused by occlusion effect occurs in the lower frequencies of the speech bandwidth. This transfer function is only an approximation of the SPL increase caused by occlusion effect, but it is generally consistent with other similar measurements made by [2] or [3].…”
Section: An Active Hearing Protection Device For Musicians Introductionsupporting
confidence: 76%
“…Furthermore, while it is gratifying to know that a hollow earmold could reduce the OE, it is unclear if this OE reduction comes at a ''cost'' to the wearers. At least in a solid earmold, Kuk et al (2005) showed that while an increase in vent diameter led to a decrease in OE, it also decreased the amount of maximum available gain and increased the contribution of direct sounds at the eardrum. These changes could affect the performance of the hearing aids.…”
mentioning
confidence: 98%
“…Another solution is the use of vents. For example, Kuk et al (2005) showed a systematic decrease in the OE as the vent diameter of an earmold was increased. The amount of reduction was best characterized by a decaying function with the most OE reduction when the vent was first introduced (from 0-1 mm).…”
mentioning
confidence: 99%
“…Participants made a judgment on sound quality, not specifically occlusion, after repeating only one sentence. Therefore, the study is not a perfect example of self-perceived occlusion for those wearing hearing aids (Kuk, Keenan, & Lau, 2005). Kiessling, Brenner, Jespersen, Groth, and Jensen (2005) quantified the occlusion effect with conventional ear molds, shell type ear molds with a novel vent design with equivalent cross-sectional vent areas, and non-occluding soft silicone ear tips.…”
Section: While Talking or Chewing Vibrations Normally Escape Throughmentioning
confidence: 99%